2016
DOI: 10.1080/14656566.2016.1236914
|View full text |Cite
|
Sign up to set email alerts
|

New and developing chemical pharmacotherapy for treating hormone receptor-positive/HER2-negative breast cancer

Abstract: Introduction: Endocrine therapy is the mainstay of treatment for a substantial proportion of hormone receptor positive (HR+) breast cancer (BC). Indeed, patients with metastatic disease not immediately life threatening may experience long disease control across several lines of endocrine therapy. The major limitation of this therapeutic approach is primary or acquired resistance. A better understanding of endocrine resistance has resulted in newer targeted agents to be added to endocrine therapy. Areas covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Given the complexity of these treatments, the identification of patient and tumor characteristics that can help inform when to use CDK4 & 6 inhibitors in the treatment paradigm and in which patients is a subject of considerable interest. 13,20,21 CDK4 & 6 inhibitor trials published to date have demonstrated treatment benefit for the addition of a CDK4 & 6 inhibitor to ET across all patient subgroups. 7-10,12,22 The present analyses of abemaciclib aim to determine independently prognostic subgroups, characterize the benefit of the addition of abemaciclib to endocrine therapy in these subgroups, and then determine those which derived the largest benefit from abemaciclib and those for which endocrine monotherapy may be an appropriate initial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of these treatments, the identification of patient and tumor characteristics that can help inform when to use CDK4 & 6 inhibitors in the treatment paradigm and in which patients is a subject of considerable interest. 13,20,21 CDK4 & 6 inhibitor trials published to date have demonstrated treatment benefit for the addition of a CDK4 & 6 inhibitor to ET across all patient subgroups. 7-10,12,22 The present analyses of abemaciclib aim to determine independently prognostic subgroups, characterize the benefit of the addition of abemaciclib to endocrine therapy in these subgroups, and then determine those which derived the largest benefit from abemaciclib and those for which endocrine monotherapy may be an appropriate initial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Three hydroxamate-type pan-HDAC inhibitors have been approved by the US Food and Drug Administration (FDA) to date for the treatment of the following cancers: SAHA for the advanced forms of cutaneous T-cell lymphoma (CTCL) 5 , 6 , 32 ; Belinostat (Beleodaq) for refractory peripheral T-cell lymphoma (PTCL) 33 ; Panobinostat (Farydak) for the combinatorial treatment of multiple myeloma 34 . Furthermore, the cyclic depsipeptide FK228 (Romidepsin) was licensed by the US FDA for the treatment of CTCL 5 , 6 , 32 , and the 2-aminobenzamide-type HDAC inhibitor MS-275 (Entinostat), for breakthrough therapy in the treatment of advanced breast cancers 35 . On the other hand, HDAC inhibitors have emerged as an attractive therapeutic candidate for neurodegeneration in the last decade 36 , 37 because therapeutic options for neuroprotective therapies in subacute or chronic ischemic stroke currently remain very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Since PI3K/AKT signaling pathway is one of the mechanisms underlying hormonal therapy resistance in advanced breast carcinoma, PI3K inhibitors were used in combination with fulvestrant or tamoxifen. Buparlisib, an inhibitor of a pan-isorform class I PI3K, taken orally, increased PFS in association with fulvestrant in postmenopausal women with advanced or metastatic estrogen receptor (ER) positive HER-2 negative breast cancer harboring PIK3CA mutations in a phase III clinical trial [ 121 , 122 ]. Buparlisib, is already being studied (phase IB) in association with lapatinib, a dual tyrosine kinase inhibitor which abrogates the HER-2/neu and EGFR pathways, in HER-2 positive advanced breast cancer that is resistant to trastuzumab, since the PI3K cascade is involved in trastuzumab resistance, and early conclusions demonstrate that this association is feasible for this kind of breast cancer [ 123 ].…”
Section: Signalling Pathways Downstream Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…When PIK3CA is mutated, the association of alpelisib, another alpha-specific PI3K inhibitor and fulvestrant showed good results in a phase I study of patients with advanced ER positive breast cancer on standard therapy [ 124 ]. There is a phase III study ongoing about the association of alpelisib or placebo with fulvestrant, and it aims to evaluate the PFS in two cohorts, one on mutated PIK3CA and the other with the wild type gene, and both stratified by the presence of lung and/or liver metastases, and prior CDK4/6 inhibitors treatment [ 122 ]. Other associations are being tested and in early phases of trials, as alpelisib and exemestane and letrozole, both antitumoral combinations, alpelisib and letrozole being tested for the safety and tolerability in patients with ER+ and HER-2 negative metastatic breast cancers that do not respond to endocrine therapy [ 122 ].…”
Section: Signalling Pathways Downstream Receptor Tyrosine Kinasesmentioning
confidence: 99%
See 1 more Smart Citation